International Electron Devices Meeting 2000. Technical Digest. IEDM (Cat. No.00CH37138)
DOI: 10.1109/iedm.2000.904338
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of trapping phenomena in GaN MESFETs

Abstract: In this work we present results related to the current/voltage characteristics collapse in GaN MESFETs. Two different failure mechanisms were observed, one of them clearly consists in a positive threshold voltage shift. Traps responsible for the "current collapse" were also characterized by means of different measurement techniques. Phototransient experiments show the presence of a capture barrier of 0.1 eV while by a spectroscopic technique four photoionization energy levels were estimated. Finally, electrolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 10 publications
7
32
0
Order By: Relevance
“…The photoionization energies of the traps are between 1.8 and 2.81 eV, suggesting that the 34 For bulk GaN, using photoionization spectroscopy, Klein et al 38 found trap levels of 1.8 and 2.85 eV were responsible for hot-electron-induced current collapse in GaN metal-semiconductor field-effect transistors (GaN MESFETs). Using the same method, Meneghesso et al 39 came to the same conclusion as Klein et al, but the trap levels were found to be 1.75, 2.32, and 2.67 eV. For AlGaN/GaN HFETs, diverse results have been reported concerning the location of traps.…”
Section: Investigation Of Trap Levels Using Monochromatic Irradiationmentioning
confidence: 49%
See 1 more Smart Citation
“…The photoionization energies of the traps are between 1.8 and 2.81 eV, suggesting that the 34 For bulk GaN, using photoionization spectroscopy, Klein et al 38 found trap levels of 1.8 and 2.85 eV were responsible for hot-electron-induced current collapse in GaN metal-semiconductor field-effect transistors (GaN MESFETs). Using the same method, Meneghesso et al 39 came to the same conclusion as Klein et al, but the trap levels were found to be 1.75, 2.32, and 2.67 eV. For AlGaN/GaN HFETs, diverse results have been reported concerning the location of traps.…”
Section: Investigation Of Trap Levels Using Monochromatic Irradiationmentioning
confidence: 49%
“…Since we did observe these traps, it is very possible that thermal equilibrium was not achieved before applying the on-stress. In fact, to keep the same initial condition, we always illuminated the devices with microscope incandescent light for 3 min before the on-stress measurement, as Binari et al, 35 Klein et al, 27,38,40 and Meneghesso et al 39 have done. This process will empty all or most of the traps.…”
Section: E Trapping Mechanism Of Non-localized Hot Electronsmentioning
confidence: 99%
“…They suggested the presence (but not the location) of electron traps. Meneghesso et al [43] studied current collapse in GaN MESFETs and found a correlation between the decrease in drain current and a shift in threshold voltage. Using phototransient measurements, they attribute this collapse to trapping under the gate and in the gate-drain access region.…”
Section: B Buffer Trapping-current Collapsementioning
confidence: 99%
“…These results have been recently verified independently by other workers. 9,10 The two traps, which are responsible for current collapse in the GaN MESFET, were found to be located in the high resistivity ͑HR͒ GaN buffer layer. Photoionization spectroscopy measurements of current collapse in AlGaN/GaN high electron mobility transistors ͑HEMTs͒ revealed similar spectra, 11 indicating that the same HR-GaN traps cause collapse in these devices as well.…”
Section: Introductionmentioning
confidence: 99%